2018
DOI: 10.3389/fpsyg.2018.00115
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Modality Information Transfer: A Hypothesis about the Relationship among Prehistoric Cave Paintings, Symbolic Thinking, and the Emergence of Language

Abstract: Early modern humans developed mental capabilities that were immeasurably greater than those of non-human primates. We see this in the rapid innovation in tool making, the development of complex language, and the creation of sophisticated art forms, none of which we find in our closest relatives. While we can readily observe the results of this high-order cognitive capacity, it is difficult to see how it could have developed. We take up the topic of cave art and archeoacoustics, particularly the discovery that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 97 publications
0
11
0
4
Order By: Relevance
“…This enables us to metaphorize and metonymize, as well as to grammaticalize, and ultimately, to make languages change (see Benítez-Burraco, 2017 for discussion). They are thus also directly relevant for the consideration of cross-modality in the evolution of language, as discussed by, e.g., Cuskley and Kirby (2013) and Miyagawa et al (2018).…”
Section: Emergence Of Proto-syntax and Verbal Aggression (Insult)mentioning
confidence: 99%
“…This enables us to metaphorize and metonymize, as well as to grammaticalize, and ultimately, to make languages change (see Benítez-Burraco, 2017 for discussion). They are thus also directly relevant for the consideration of cross-modality in the evolution of language, as discussed by, e.g., Cuskley and Kirby (2013) and Miyagawa et al (2018).…”
Section: Emergence Of Proto-syntax and Verbal Aggression (Insult)mentioning
confidence: 99%
“…In summary, we can say with some confidence that the apparently human-unique capacity for language-specific syntax emerged within the last 200 kya, and we can say this thanks to the development of sophisticated tools, cultural artifacts, complex trading relationships, and paintings. Indeed Miyagawa et al (2018) draw a connection between cave paintings and “archeoacoustics,” noting that cave art is typically connected to the acoustic properties of the chambers they are located in. Being sensitive to the echoes generated in these chambers, Miyagawa et al speculate that cave paintings may have been a form of cross-modality information transfer through which acoustic signals are transformed into visual representations.…”
Section: Tool Usementioning
confidence: 99%
“…His research program in the last sixty years, which has resulted in evolving different linguistic models, has tried to make this variety in the externalization of languages compatible and coherent with their underlying cognitive unity within the innate computational system framework of Generative Grammar. This externalization of language involves 4This thesis finds support in studies about the sudden externalization of the symbolic mode of thinking found in prehistorical cave and rock art going hand in hand with the appearance of language (seeMiyagawa et al 2018).…”
mentioning
confidence: 89%